Glucose Monitoring Systems - general rules of use and chances in therapy of type 1 diabetes - Garstka, Michał; Gadomska, Anna; Kurek, Justyna; Gorzyński, Rafał; Dominik, Hanna; Czudy, Zuzanna; Pawęska, Wojciech; Molczyk-Sieńczak, Justyna; Radwański, Jan; Polatowska, Marika (Journal of Education, Health and Sport, 2023)
Introduction: Glycemic control and maintaining it within the desired range are essential for achieving therapeutic goals in patients with type 1 diabetes. Over the years, patients have gained access to advanced glycemic monitoring technologies that have revolutionized self-monitoring methods. These technologies provide data that was previously unavailable to glucometer users. They allow creating new goals to minimize the risk of diabetic complications. Purpose of the work: The goal of this study was to answer the following questions: What additional information do glycemic monitoring systems offer to patients compared to glucometers? How should this information be utilized to make therapeutic decisions? Do these systems lead to improved glycemic management? Materials and Methods: A literature review was made using PubMed, Springer Link and Google Scholar databases, searching for articles published in English and Polish up to May 2023, focusing on type 1 diabetes and glucose monitoring systems. Summary: The use of glycemic monitoring systems provides additional information compared to relying only on glucometers. Patients equipped with a glucose monitoring system can make more accurate therapeutic decisions based on a larger volume of data. Some continuous glucose monitoring systems offer additional features compatible with personal insulin pumps, preventing or reducing the intensity and duration of hypoglycemia. Patients using glycemic monitoring systems can more frequently achieve therapeutic goals.